Care work - factors affecting post 9/11 United States Army chaplains: compassion fatigue, burnout, compassion satisfaction, and spiritual resiliency - Theodore, Vance P. (Kansas State University, 2011)
This study examined the relationships between and among the factors of compassion fatigue, burnout, compassion satisfaction and spiritual resiliency in association with the care work of United States Army chaplains who minister to soldiers, families, and Department of the Army (DA) civilians in the military. This investigation breaks new ground in understanding the factors that affect chaplain care work. Data were collected from 408 active duty Army chaplains who responded to and completed the online survey. Information about rank, years of service, battle fatigue/stress and number of deployments was collected. These data along with specific scales were combined into the Chaplain Care Work Model—the tool used in this investigation. Scores from three measurement instruments: Professional Quality of Life Scale R-IV, Spiritual Well-Being Scale, and the Resilience Scale were used to test the hypotheses for this study. Of particular interest, the measurement scales of Spiritual Well-Being and Resiliency were combined to develop a new measurement construct labeled Spiritual Resiliency. The model of Chaplain Care Work was tested using path analysis and structural equation modeling techniques to illustrate the relationships of the predictors (constructed from latent variables—Chaplaincy Status, Deployment Status, and Self Care) to the outcome measure of Care Work (also a latent variable). Overall 85% of the variance in care work can be attributed to the model’s predictors, adding to the value of examining care work among those who provide direct service to others. Findings indicated that spiritual resiliency ebbed and flowed as a function of the different levels of compassion fatigue, burnout, and compassion satisfaction experienced by the chaplains because of their care work. Furthermore, number of deployments and experience (years of chaplain service) had significant relationships with compassion fatigue and burnout. Results from the findings were underpinned by explicit narrative comments provided by chaplains. These comments provided rich material in support of the significant relationships discovered in this study, and offered insights into how care work is both meaningful and necessary for maintaining a healthier chaplaincy.
Keywords: Chaplains; Military; Compassion Fatigue; Burnout; Compassion Satisfaction; Spiritual Resiliency; Individual & Family Studies (0628); Military Studies (0750); Religion (0318)